Self-reported Hypoglycaemic Events in 2 430 Patients with Insulin-treated Diabetes in the German Sub-population of the HAT Study - Kern, Werner; Holstein, Andreas; Moenninghoff, Christian; Kienhöfer, Joachim; Riedl, Matthias; Kulzer, Bernhard (Experimental and Clinical Endocrinology & Diabetes, 2017)
Data concerning true hypoglycaemic incidence in insulin-treated patients with diabetes in real-world clinical practice are lacking in Germany. The aim of this analysis was to determine the incidence of hypoglycaemia experienced by the German cohort of patients enrolled in the global Hypoglycaemia Assessment Tool (HAT) study. This was a non-interventional, 6-month retrospective and 4-week prospective study using self-assessment questionnaires and patient diaries assessing patients aged ≥18 years in Germany, with type 1 diabetes (T1D) (n=811) or type 2 diabetes (T2D) (n=1 619) treated with insulin for >12 months. The primary endpoint was the percentage of patients experiencing ≥1 hypoglycaemic event during the prospective observational period (4 weeks after baseline). Predictive and continuous factors (such as age, gender, duration of insulin use and HbA1c) contributing to hypoglycaemia risk were explored.During the prospective period, at least one hypoglycaemic event was reported by 81.3% of patients with T1D and 39.7% of patients with T2D, indicating that hypoglycaemia is a common acute complication among patients with insulin-treated diabetes. Severe hypoglycaemia was reported by 9.1% of patients with T1D and 5.4% of patients with T2D. Higher rates of any and severe hypoglycaemia were reported prospectively than retrospectively, regardless of diabetes type, indicating that patients retrospectively under-report hypoglycaemia. Prospective rates (events per patient-year) of any, nocturnal and severe hypoglycaemia were 80.3, 9.9 and 3.0 for T1D and 15.6, 2.4 and 1.1 for T2D, respectively. Given the potential for recall bias in retrospective reporting, this prospective assessment of hypoglycaemia appears more reliable than retrospective assessment.Trial number: NCT01696266
Keywords: hypoglycaemia; real-world; severe; nocturnal; Germany